(untitled) (Información, cultura y sociedad, 2004)
The existing relationship between the achieved automation level and the use of new technologies to provide high value-added services, in the context of public libraries in the Ciudad Autónoma de Buenos Aires and surrounding areas is studied. It presents a diagnosis of the current situation, aiming to determine whether these information units are prepared to respond to the needs of the community they serve within the information society. A survey with closed questions is applied based on the following categories: general information, resources, library automation, bibliographic control, networks integration, services, and financing sources. Research is made upon 73 responses provided by the libraries surveyed. The analysis verifies the lack of use of standards looking towards information exchange and the distributed processing of information, the abscence of information quality control, the limited exploitation of new information and communication technologies.